Comparison of metabolite profile of aflatoxin-contaminated yellow and white maize Ogi after fermentation with lactic acid bacteria and yeast - Aribisala, O.R. (University of Ibadan, 2021)
Aflatoxins are a group of highly toxic, mutagenic, teratogenic, and carcinogenic secondary metabolites of Aspergillus species including Aspergillus flavus and Aspergillus parasiticus. Maize is susceptible to aflatoxin contamination; so, ogi, (fermented maize gruel) consumed as a breakfast cereal, weaning food and food for convalescents is prone to aflatoxins. Therefore, targeted fermentation of yellow and white maize, for ogi, was investigated as a means of aflatoxin decontamination in ogi. Methods and Results: Limosilactobacillus fermentum W310 and Candida tropicalis YY25 were isolated and characterized phenotypically and genotypically from spontaneously fermenting yellow and white maize ogi and then used for targeted fermentation in white maize. Isolate safety was determined via in vitro assessment of the probiotic potential of the isolates including tolerance to bile salts and acidification tests. Aflatoxin concentrations were determined via thin layer chromatography, uncontaminated maize grains were dry milled, processed into slurry and inoculated with either toxigenic A. flavus La3288 or atoxigenic A. flavus La3279 in triplicates. A control sample without L. fermentum W310 or C. tropicalis YY25 was included. Fermentation with L. fermentum W310 reduced aflatoxin B1 and B2 by 86% and 75% whereas C. tropicalis YY25 reduced aflatoxin B1 and B2 by 60% and 31% respectively. After fermentation, amino acid profile was determined by standard methods using high performance liquid chromatography. A total number of seventeen amino acids were found including; aspartic acid, serine, glutamine, glycine, histidine, threonine, arginine, alanine, proline, cystine, tyrosine, valine, methionine, lysine, iso-leucine, leucine and phenyl-alanine. There were significant differences in the levels of the amino acid metabolites produced by the different treatments suggesting that there is a difference in the utilization and accumulation of these compounds by the microorganisms involved in the fermentation process. Significance and Impact of the study: Targeted fermentation is useful for decontamination of aflatoxin contaminated maize. In the current study, the use of L. fermentum and C. tropicalis strains with probiotic potentials is beneficial in the biodetoxification of aflatoxins in ogi.